Pelatihan Pembelajaran Inovatif, Penyusunan Perangkat Pembelajaran dan Pembukuan Pada Bunda PAUD - Endah Hendarwati; Aristiana Prihatining Rahayu; Aris Setiawan (Aksiologiya: Jurnal Pengabdian Kepada Masyarakat, 2017)
The activity of IbMitra is held in two different places, within one Surabaya area, in the Paud Mutiara Bunda group in Mojo and the Paud Cahaya Bunda group behind the red railway Stage in Surabaya city of East Java Province. Each group has students of approximately 15 and 39 children. The problems of partners 1 and 2 are the limited educational game tools, the teacher's ability to build the tools and learning activities, and the speed with which Paud operates. The main objectives and objectives of IbM Paud Cahaya Bunda and Mutiara Mother's activities are to provide knowledge to early childhood teachers about learning methods, how to create learning tools, Paud management and procurement of educational tools for early childhood education. The targets of the activities are Master Paud Cahaya Bunda and Mutiara Bunda for tools and methods appropriate for early childhood, as well as assist the procurement of PAUD infrastructure facilities. The methods used in this meeting are discussion, group discussion, question and answer, demontration and brainstorming. The solutions offered are related to the skills and management for these two groups of Early Childhood Mothers and Mothers of the Lady; (1) training and assistance in the preparation of instructional tools; (2) training on the use of learning methods in early childhood; (3) training in the use of educational games for early childhood; (4) training and administrative assistance; (5) assist in the provision of educational games. The output of IbM program is a way of improving the quality of learning process, improving the skill of arranging learning tools, management, educational game tools and scientific publication in Journals with ISSN.